Peculiarities Of The Integration Of Linguistics And Medicine - KadirovnaAbuzalova, Mekhriniso; Gaybullaeva, Nafisa Izatullayevna (The journal of contemporary issues in business and government, 2021)
Today, the replenishment of the vocabulary of our national language, the creation of Uzbek alternatives to modern terms in medicine, the creation of their electronic versions, the development of problems of linguistics and the study of language, personality, social relations in medicine are topical. To enrich the vocabulary of Uzbek terminology, coverage of terms using nominatives, providing meaningful explanations filling inappropriate medical terms with unique medical nominations, widespread use of the native language in their creation serve to develop and perfect the Uzbek language.